The Role of Athletic Activities in Early Childhood Development: An Evidence Based Literature - Setiani, Rahma Azizah; Habibi, Zaki Anwar; Hakim, Naufal Nur; Azzaki, Muhamad Fatih; Nurrachmad, Limpad (STKIP Taman Siswa Bima, 2025)
This study examines the contribution of athletic activities to early childhood development through a literature review of 20 peer reviewed scientific articles published between 2018 and 2025. Articles were retrieved from reputable national and international databases including Google Scholar SINTA DOAJ and ScienceDirect and selected through a structured screening process based on predefined inclusion and exclusion criteria. Data were analyzed using a thematic analysis approach to identify key developmental outcomes. The findings indicate that structured and game based athletic activities effectively enhance muscle strength motor coordination balance self confidence and social skills in early childhood. Game based athletic learning was consistently found to be more effective than formal instructional approaches in supporting both physical and psychosocial development. This review highlights the importance of integrating athletic activities into early childhood physical education through developmentally appropriate and adaptive learning designs and provides practical recommendations for educators to implement game based athletic learning strategies.